Carbon black, multiwall carbon nanotubes, expanded graphite and functionalized graphene flame retarded polypropylene nanocomposites. (9th July 2013) - Dittrich, Bettina; Wartig, Karen‐Alessa; Hofmann, Daniel; Mülhaupt, Rolf; Schartel, Bernhard
Abstract : Herein, we examine the influence of adding functionalized graphene (FG), distinct expanded graphites and carbon nanofillers such as carbon black and multiwall carbon nanotubes on mechanical properties, morphology, pyrolysis, response to small flame and burning behavior of a V‐2 classified flame‐retarded polypropylene (PP). Among carbon fillers, FG and multilayer graphene (MLG) containing fewer than 10 layers are very effectively dispersed during twin‐screw extrusion and account for enhanced matrix reinforcement. In contrast to the other fillers, no large agglomerates are detected for PP‐FR/FG and PP‐FR/MLG, as verified by electron microscopy. Adding FG to flame‐retardant PP prevents dripping due to reduced flow at low shear rates and shifts the onset of thermal decomposition to temperatures 40°C higher. The increase in the onset temperature correlates with the increasing specific surface areas (BET) of the layered carbon fillers. The reduction of the peak heat release rate by 76% is attributed to the formation of effective protection layers during combustion. The addition of layered carbon nanoparticles lowers the time to ignition. The presence of carbon does not change the composition of the evolved pyrolysis gases, as determined by thermogravimetric analysis combined with online Fourier‐transformed infrared measurements. FG and well‐exfoliated MLG are superior additives with respect to spherical and tubular carbon nanomaterials. Copyright © 2013 John Wiley & Sons, Ltd.